2011
DOI: 10.1007/s00418-011-0885-0
|View full text |Cite
|
Sign up to set email alerts
|

P2Y purinoceptors induce changes in intracellular calcium in acinar cells of rat lacrimal glands

Abstract: Adenosine 5'-triphosphate (ATP) is an extracellular signal that regulates various cellular functions. Cellular secretory activities are enhanced by ATP as well as by cholinergic and adrenergic stimuli. The present study aimed to determine which purinoceptors play a role in ATP-induced changes in the intracellular concentration of calcium ions ([Ca²⁺](i)) and in the fine structure of acinar cells of rat lacrimal glands. ATP induced exocytotic structures, vacuolation and an increase in [Ca²⁺](i) in acinar cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 47 publications
1
15
0
6
Order By: Relevance
“…Із цієї групи, в базальній мембрані ацинарних клітин сльозових залоз мишей, екс пресуються Р2Y 11 і Р2Y 13 -рецептори [36]. АТР-індуковані відповіді ацинарних клітин сльозових залоз щурів реалізуються (поряд з активацією P2X-рецепторів) переважно через активацію P2Y 1 -рецепторів і наступну ІР 3 -опосередковану мобілізацію Са 2+ , що пока-зано з використанням гепарину та інгібітору фосфоліпази С -U73122, а також зворотної транскриптазної полімеразної ланцюгової реакції [20].…”
unclassified
See 2 more Smart Citations
“…Із цієї групи, в базальній мембрані ацинарних клітин сльозових залоз мишей, екс пресуються Р2Y 11 і Р2Y 13 -рецептори [36]. АТР-індуковані відповіді ацинарних клітин сльозових залоз щурів реалізуються (поряд з активацією P2X-рецепторів) переважно через активацію P2Y 1 -рецепторів і наступну ІР 3 -опосередковану мобілізацію Са 2+ , що пока-зано з використанням гепарину та інгібітору фосфоліпази С -U73122, а також зворотної транскриптазної полімеразної ланцюгової реакції [20].…”
unclassified
“…Також було ідентифіковано [20] (крім Р2Y 1 ) у секреторних клітинах сльозових за-лоз P2Y 2,4,12,14 , але не підтвердили експресії Р2Y 11 і Р2Y 13 -рецепторів. Питання про те, через які саме підтипи P2Y-рецепторів опосередковується механізм сигнальної трансдукції під впливом АТР є дуже важли-вим, адже механізм сигнальної трансдукції під час активації різних Р2Y-рецепторів може за-лучати різні сигнальні шляхи [8,37,38].…”
unclassified
See 1 more Smart Citation
“…For this purpose, we examined the [Ca 2+ ] i dynamics in semi-intact rat acinar cells that retained their essential cellular structure. We recently showed that ATP and protease-activeted receptor 2 participate in a variety of signaling activities in lacrimal glands (40,49). The present study focused on identification of the types of adrenoceptors that are present in acinar cells and the receptors that mediate the effect of NA on [Ca 2+ ] i levels in these cells.…”
Section: +mentioning
confidence: 96%
“…We recently reported that Ca 2+ mobilization from intracellular Ca 2+ stores is induced by extracellular ATP, suggesting the presence of metabotropic receptors that are activated by ATP in rat lacrimal gland acinar cells (40). Purinergic receptors are important signaling molecules that are activated by ATP.…”
Section: Muc Mrna Expression In Lacrimal Gland Acinar Cellsmentioning
confidence: 99%